Performance of Sugarcane Planted at Different Soil Types and Rainfall Duration in the Philippines - Oñal, Jr., Paulino A.; Baldonebro, Jessel Jane G.; Andrade, Francis E. (Future Science / FSH-PH Publications, 2025)
The present status of sugarcane farming in the Philippines is very low at an average of 57.36 tons per hectare (TC/ha), way below the national target of 75 TC/ha For the seven location covered by this study the total area planted is 93,354.03 hectares with an average 54.35 TC/ha. This study used the descriptive method and in the gathering of data the instrument prepared by Oñal (2021) was utilized. For this study, 320 sugarcane farmers were randomly identify as respondents. High significant difference is shown with the level of production of sugarcane at the Visayas, Philippines when group by location with a mean of 2.28 (5%). Furthermore, the level of production as influence by the duration of rainfall was statistically significant at 1% level with a production mean of 2.26. Relatively, the level of production of sugarcane planted at different type of soil is statistically significant as well, at 1% level with a production mean of 2.43. The further revealed that there is a signification correlation between the sugarcane production and the duration of rainfall as well as the production and the type of soils at 1% level of significant respectively. The results of the study indicates that in order to increase the production of sugarcane it is best to plant the crop in a loamy or mixed soil. If the area has no irrigation-facilities, the timing of planting should be religiously observe so that sugarcane plant can receive the rainfall in a period of 5 months or more within its entire growing period.